2019
DOI: 10.1089/g4h.2017.0181
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Games as a New Class of Physical Activity Interventions? The Impact of Pokémon Go Use and Gaming Intensity on Physical Activity

Abstract: In this pilot study, Pokémon Go was associated with a transient increase in physical activity in the first week. Augmented reality games need to demonstrate a sustained positive health impact to be promoted as a new class of physical activity interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Although this study recruited a large national sample, it involved participants using only an iPhone 6. Another study [13] found similar results of increased walking distance during the first week of playing PG, but no difference in the activity levels beyond the first week of playing. this study utilized iPhones to track walking distance and had a control group.…”
Section: Introductionmentioning
confidence: 64%
“…Although this study recruited a large national sample, it involved participants using only an iPhone 6. Another study [13] found similar results of increased walking distance during the first week of playing PG, but no difference in the activity levels beyond the first week of playing. this study utilized iPhones to track walking distance and had a control group.…”
Section: Introductionmentioning
confidence: 64%
“…Given the substantial health care costs of self-harm, it is imperative to address and attempt to alleviate psychosocial difficulties before individuals harm themselves. Although Pokémon Go has been studied in outdoor settings for physical activity outcomes [26,27,30,34,35], there has been limited research on the effects of Pokémon Go on mental health (in particular, on its potential as a tool for the prevention of mental health disorders). Pokémon Go may lead to decreases in the frequency of self-harm by encouraging behaviors that improve mental health; however, no prior research has tested this hypothesis.…”
Section: Principal Findingsmentioning
confidence: 99%
“…The opportunity to engage casually with others in public has been found to mitigate feelings of loneliness because of an increased sense of belonging in the community [33]. Previous studies [30,34,35] focus on individual-level changes in physical activity, and little is known about the influences of Pokémon Go at the population level especially in Hong Kong where population is large but public spaces are limited; therefore, we carried out a quasi-experimental evaluation to examine any changes in the incidences of self-harm and other injury and noninjury events in Hong Kong after the launch of Pokémon Go.…”
Section: Introductionmentioning
confidence: 99%
“…There has been some public interest in a recent active videogame, Pokémon Go, an augmented reality game (i.e., fictitious elements superimposed on video images of the real world using smartphones) 58 . Pokémon Go substantially increased PA 59 among players for up to 1 week after they started playing the game. In 2 different studies, 60 enjoyment of playing Pokémon Go was a primary predictor of PA.…”
Section: What Might Be Done To Increase Chinese Children's Level Of Pa?mentioning
confidence: 99%